THE INFLUENCE OF YOUTUBE ON STUDENT CREATIVITY IN ART CULTURE AND WORKS (SBdP) LESSONS IN THE COVID-19 PANDEMIC - Sisriawan Lapasere; Herlina Herlina; Dedi Rore Poting (Universitas Tadulako, 2021)
This study aims to determine the effect of the use of YouTube social media on student creativity in the fourth grade subjects of cultural arts and crafts (SBdP) at SDN Nunu. This research is a quantitative study using an experimental approach using two groups, namely the experimental class group and the control class group. The design used in this research is the design